Investigation of adsorption of 5-Chlorouracil onto montmorillonite: An IR and Raman spectroscopic study - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier, 2018)
In this study, the adsorption of 5-Chlorouracil (5-ClU) on natural montmorillonite from Anatolia was investigated using FT-IR and Raman spectroscopy. The 5-ClU is a thymine antagonist and has some antitumor properties. The comparison of the vibrational spectra of the adsorbed 5-ClU with those of the free molecule provided data on the nature and characteristics of the clay organic complexes. The intercalation of 5-ClU within montmorillonite has been shown by X-ray diffraction to increase the interlayer spacing. Vibrational spectroscopy indicates that adsorbed 5-ClU molecules on montmorillonite are coordinated to exchangeable cations, directly or indirectly through water bridges.
Keywords: Adsorption; Clays; 5-Chlorouracil; FTIR; Raman